Two domains at the origin are required for replication and maintenance of broad-host-range plasmid R1162. - Kim, Y J (1987)
Two domains at the replicative origin of broad-host-range plasmid R1162 are required in cis for plasmid maintenance in Escherichia coli and for plasmid DNA replication in cell extracts. Increasing the distance between the domains reduces replication in vitro, without substantially changing plasmid DNA content or stability in vivo.